TOGAF's Approach in Developing an Enterprise Architecture for the Information Technology Security Industry - Hidayat, Rachmad Syarul; Indrajit , Richardus Eko; Dazki, Erick (Journal La Multiapp, 2024)
The information technology security industry, encompassing various activities such as risk identification and assessment, policy development, and solution implementation, plays a crucial role in maintaining the integrity and security of information systems. This study aims to develop and implement an efficient and effective enterprise architecture within the information security sector, focusing on three key core processes identified as the major revenue contributors: risk identification and assessment, security policy development, and security solution implementation. Utilizing the TOGAF-based Enterprise Architecture framework, this research identifies and designs architecture that integrates various systems, applications, and business processes, facilitating better alignment within the organization. The architecture design process involves a thorough analysis of operational needs and business strategies, leading to the development of a model that enhances efficiency and reduces the risk of failure in technology implementation. The outcomes of this study are intended to provide practical guidance for information security companies to optimize operations, simplify system complexities, and achieve strategic goals more effectively. It is anticipated that the application of the designed architecture will have a significant positive impact on the company's ability to address challenges and dynamic needs within the information security industry.